Republic of Latvia : Selected Issues. (IMF Staff Country Reports; Country Report, 2018)
This Selected Issues paper analyzes labor market challenges in Latvia. In the boom period leading up to the global financial crisis, the economy experienced widespread labor shortages and soaring wage growth. The bursting of the bubble led to a deep recession, high unemployment, and a sharp contraction in wages. With the economy now in its eighth year of recovery, Latvia is once again experiencing a tightening labor market-a situation exacerbated by unfavorable demographic trends. Latvia's future prosperity will depend critically on whether it is able to address its labor market challenges. Employment protection legislation (EPL) is relatively restrictive. EPL refers to the procedures and costs associated with hiring and dismissing workers. Theory suggests that overly restrictive EPL reduces both job creation and job destruction and may slow productivity growth by raising labor adjustment costs for firms. Latvia's tightening labor market calls for reforms that make the most of the country's human resources. Reforms should aim to tackle barriers to employment, encourage more labor market participation, help Latvia's citizens build new skills, and stem the decline in the working-age population.